Ghana, Savelugu-Nanton Household Survey Dataset, 2001 - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
In 2000, UNICEF–Ghana and IFPRI agreed upon a program of action research to evaluate the scope for food-based strategies to reduce micronutrient undernutrition in Ghana. The food-based strategies were planned as one component of UNICEF’s broader Integrated Community Based Development (ICBD) program. Although UNICEF had been operating its ICBD program in other districts, the food-based micronutrient strategies were first introduced as part of the ICBD program in Savelugu/Nanton District. The 2001 Ghana Savelugu-Nanton Survey is one of the early steps in the program of action research to evaluate the effectiveness of food-based strategies to increase the consumption of micronutrient-rich foods, especially among young children and women of reproductive age. The survey interviewed 1,684 households living in 64 communities, and collected information about agricultural production, food consumption, nutritional status, use of credit, education, community infrastructure and services, and a range of other topics. The 2001 survey provides baseline information on conditions that existed prior to the implementation of the program interventions. A follow-up survey was conducted in 2004 to evaluate the impact of the program not only on the consumption of micronutrient-rich foods, but also on a number of other outcomes of interest, including access to and use of credit, children’s nutritional status, women’s control of resources, and household incomes.